Inset Feed Toppled H-Shaped Microstrip Patch Antenna for PCS/WiMAX Application - Mohammad Aneesh; Mohd. Gulman Siddiqui; Jamshed Aslam Ansari; Ashish Singh; Km. Kamakshi (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
In this paper, an inset feed toppled H-shaped microstrip patch antenna with grounded plane is investigated for triple band operation. The simulation of proposed antenna geometry has been performed using IE3D simulation software based on method of moment. The prototype of the proposed antenna has been fabricated and tested to validate the simulation work. The measured results indicate that the reflection coefficient is better than -10dB for 1.8 GHz (PCS), 3.5 GHz (WiMAX), and 5.5 GHz (WiMAX) frequencies.